Det legemlige promissio: Socialitet som nøgle til Luthers nadverskrifter - Holm, Bo Kristian (Dansk Teologisk Tidsskrift, 2023)
This article presents a systematic-theological reading of the historical development of Luther’s theology of the Lord’s Supper. It is argued that a focus on the social dimension in Luther’s writing about the Lord’s Supper reveals a thread that goes through all the phases of Luther’s writings on the Lord’s Supper: From a clear focus on the social life in the congregation in 1519, over a focus on the Lord’s Supper as integrating the sinner in the new fellowship with Christ, to a promissional understanding of the real presence of Christ in bread and wine. As a result, the social dimension of the Lord’s Supper is located in the orders of the world, highlighting the sacramental realism in Luther’s theology.